Influence of the Assembly Method on the Cell Current Distribution of Series–Parallel Battery Packs Based on Connector Resistance - Chang, Long; Ma, Chen; Luan, Chunxiao; Sun, Zhezhe; Wang, Cunyu; Li, Hongyu; Zhang, Yulong; Liu, Xiangqi (Frontiers in Energy Research, 2022)
In order to meet the energy and power requirements of large-scale battery applications, lithium-ion batteries have to be connected in series and parallel to form various battery packs. However, unavoidable connector resistances cause the inconsistency of the cell current and state of charge (SoC) within packs. Meanwhile, different assembly methods and module collector positions (MCPs) may result in different connector resistance arrangements, thereby leading to different cell current distributions. Therefore, the correlation of connector resistance to battery pack performance is worth investigating. Based on the simplified equivalent circuit model (ECM), the mathematical models of cell current distribution within packs under different assembly methods are obtained in this paper. Then, we use COMSOL Multiphysics simulation to analyze the guidelines of series assembly for parallel modules and then study the influences of connector resistance and MCP on series–parallel battery packs. The results show that the assembly method with an equal distance between each cell and the assembly contact surface for series assembly can effectively reduce the inhomogeneous current. However, the cell current and SoC distribution within the series–parallel battery pack is completely independent of the Z-configuration and ladder configuration. In addition, for series–parallel battery packs, the non-edge parallel module part of the series–parallel battery pack can be replaced with a series cell module (SCM) structure. Finally, the influences of the value of the connector resistance and current rate on the cell current distribution are discussed.